Papua New Guinea : Country Gender Assessment, 2011-2012 - World Bank (Washington, DC, 2014)
Papua New Guinea (PNG) became independent in 1976 as a constitutional parliamentary democracy. The country has four regions (Highlands, Islands, Momase and Southern) and 21 provinces including the autonomous region of Bougainville and two new provinces recently created in the southern and western parts of the highlands region. Another province-level division is the National Capital District, which comprises the capital city, Port Moresby. Each province is divided into electorates that vote for members of parliament as well as for a provincial member of parliament, who serves as the governor of the province. The country has a population of just over seven million, with an estimated population growth rate of 2.8 percent. Nearly half of PNG's population is under the age of 20 and the number of young people is expected to double in the next 20 years. Youth unemployment is high and rising, with only one in ten school graduates finding jobs in the private sector. With many young people leaving their villages in search of jobs in the towns and cities, there is a shortage of employment opportunities, which has contributed to the expansion of (mainly male) urban youth gangs, exacerbating problems of law and order.